Legal Protection for Consumers of Unit Link Life Insurance Products - Wijaya Nugroho, Robert; Marzuki, Yusron (International Journal of Social Science, Education, Communication and Economics, 2024)
Insurance is a non-bank financial institution which has the main function of distributing and distributing risks by collecting funds or also known as premiums obtained from the public or companies by marking an agreement or policy in which there is various information regarding the agreement between the insurer and the policy holder which has the aim of positive for various parties. These various parties are insurance companies, policy holders and the government. Because of this positive goal, the existence of this insurance must be maintained and expanded along with its development. The manifestation of this supervision is manifested in several factors such as statutory regulations, understanding of the community, good faith on both parties and the professionalism of an insurance marketing personnel. The aim of this research is to identify legal certainty for consumers who purchase unit-linked life insurance products which are analyzed based on existing and applicable laws and regulations in Indonesia. This type of research is normative juridical, namely a type of research approach to laws and regulations that is linked to the existing case, namely the number of unit link policy holders who complained to the Financial Services Authority about the money in the policy running out or not in accordance with the explanation from the life insurance company marketing staff since 2019 until this writing was written.